2016
DOI: 10.1027/0227-5910/a000391
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence Rates of Deliberate Self-Harm in Denmark 1994–2011

Abstract: Abstract. Background: The validity and reliability of suicide statistics have been questioned and few nationwide studies of deliberate self-harm have been presented. Aim: To calculate rates of deliberate self-harm in Denmark in order to investigate trends and assess the reliability of hospital records. Method: A register study based on all individuals recorded with an episode of deliberate self-harm or probable deliberate self-harm in nationwide registers during 1994–2011. Results: A substantial difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 39 publications
5
63
2
5
Order By: Relevance
“…[25][26][27] A threefold increased rate of probable and deliberate self harm was reported in females aged 10-19 years from 1994 to 2011 in a Danish hospital registry study. 27 Another UK based study of primary care data from The Health Improvement Network (THIN) found that the intentional incidence of poisoning in females aged 15-17 years increased from 39.1 to 46.6 per 10 000 person years between the two successive calendar periods, 1992-96 to 2007-12. 25 Recent data from the adult psychiatric morbidity survey in England, 28 based on clinical interviews, indicate that 11.7% of [16][17][18][19][20][21][22][23][24] year old females in 2007 reported ever self harming, increasing to 19.7% in 2014.…”
Section: Temporal Trends In Sex and Age Specific Incidencementioning
confidence: 99%
“…[25][26][27] A threefold increased rate of probable and deliberate self harm was reported in females aged 10-19 years from 1994 to 2011 in a Danish hospital registry study. 27 Another UK based study of primary care data from The Health Improvement Network (THIN) found that the intentional incidence of poisoning in females aged 15-17 years increased from 39.1 to 46.6 per 10 000 person years between the two successive calendar periods, 1992-96 to 2007-12. 25 Recent data from the adult psychiatric morbidity survey in England, 28 based on clinical interviews, indicate that 11.7% of [16][17][18][19][20][21][22][23][24] year old females in 2007 reported ever self harming, increasing to 19.7% in 2014.…”
Section: Temporal Trends In Sex and Age Specific Incidencementioning
confidence: 99%
“…Rates of hospital-treated self-harm have been found to be particularly raised in adolescents compared to older age groups. Studies examining emergency department (ED) visits in Western countries (including Ireland, the US, Denmark and the UK) have found the highest rates of self-harm among girls aged between 15 and 19 years [5][6][7][8][9]. A substantial body of evidence indicates that economic recession and its aftermath is associated with increases in rates of suicide and self-harm, though much of this work focuses on the working-age population [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing temporal trends in mental health between countries is an important step in understanding possible risk and protective factors at population level [15]. In Denmark, increasing rates of self-harm in females aged 15-19 between 1994 and 2011 [9] and from 1994 to 2003 in girls (and, to a lesser extent, boys) aged 10-16 [16] have been reported. However, it has yet to be determined if these trends continued into recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnoses with epilepsy (ICD-8 293.2 and ICD-10 G40-41), alcohol abuse 303.x9,303.20,303.28,303.90,, illicit drug use 304.x9,) and prior suicide attempts/self-harm (Reuter Morthorst et al, 2016) were identified from the DPCRR and the National Patient Register (NPR), the latter containing information on somatic diagnoses from in-and outpatient and emergency room contacts at somatic hospitals (Lynge et al, 2011). Information on age at first psychiatric hospital contact with bipolar disorder and prior psychiatric contacts were also obtained from the DPCRR (Mors et al, 2011).…”
Section: Descriptive Variablesmentioning
confidence: 99%